Risk of illness among construction professionals - Rosana Amora Ascari; Priscila Locatelli; Katrini dos Santos Conteratto; Clodoaldo Antônio De Sá; Liana Lautert (Universidad de Alicante, 2019)
Objective: To evaluate the risks of sickness present in the work activities of construction workers and the factors associated with the risk of illness in this population. Methods: This is a cross-sectional research with a quantitative approach, through the Inventory of Work and Illness Risks. Participated 75 workers linked to a construction company, after approval by the Research Ethics Committee under CAAE n.º 22445413.3.0000.0118. Results: There was a predominance of males, between 18 and 28 years of age, married, with low schooling, with 6 to 10 years of profession. Emphasis is given to the factors: Conditions of Work, Physical Cost and Lack of Recognition, which had "negative, severe" evaluation, characterizing human cost production and labor suffering. Results: The results point out risks of illness among construction professionals. Conclusion: It is necessary to review the working conditions in the scenario investigated in order to reduce the risk of illness among construction workers.